We need both natural and energy solutions to stabilize our climate. (22nd March 2019) - Griscom, Bronson W.; Lomax, Guy; Kroeger, Timm; Fargione, Joseph E.; Adams, Justin; Almond, Lucy; Bossio, Deborah; Cook‐Patton, Susan C.; Ellis, Peter W.; Kennedy, Christina M.; Kiesecker, Joseph
Abstract : We respond to concerns raised by Baldocchi and Penuelas who question the potential for ecosystems to provide carbon sinks and storage, and conclude that we should focus on decarbonizing our energy systems. While we agree with many of their concerns, we arrive at a different conclusion: we need strong action to advance both clean energy solutions and natural climate solutions (NCS) if we are to stabilize warming well below 2°C. Cost‐effective NCS can deliver 11.3 PgCO2 e yr ‐1 or 30% of near‐term climate mitigation needs through protection, improved management, and restoration of ecosystems, as we increase overall ambition.